2016
DOI: 10.3168/jds.2015-10501
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Multi-trait estimation of genetic parameters for milk protein composition in the Danish Holstein

Abstract: Genetic parameters were estimated for the major milk proteins using bivariate and multi-trait models based on genomic relationships between animals. The analyses included, apart from total protein percentage, αS1-casein (CN), αS2-CN, β-CN, κ-CN, α-lactalbumin, and β-lactoglobulin, as well as the posttranslational sub-forms of glycosylated κ-CN and αS1-CN-8P (phosphorylated). Standard errors of the estimates were used to compare the models. In total, 650 Danish Holstein cows across 4 parities and days in milk r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 13 publications
9
24
3
Order By: Relevance
“…Polymorphism and milk quality studies have been widely used in the optimization of dairy population, and the link between milk composition and genetic variation in milk production has a profound impact on dairy production [2,3,24,25]. Recently, Poulsen et al found that α-LA is a major component, which has negative effect on milk coagulation in Danish Jersey [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphism and milk quality studies have been widely used in the optimization of dairy population, and the link between milk composition and genetic variation in milk production has a profound impact on dairy production [2,3,24,25]. Recently, Poulsen et al found that α-LA is a major component, which has negative effect on milk coagulation in Danish Jersey [26].…”
Section: Discussionmentioning
confidence: 99%
“…Milk protein components have an important influence on milk production traits [1], and mainly affect by genetic factors [2,3]. There are six major milk protein components (α S1 -CN, α S2 -CN, β-CN, κ-CN, α-LA, and β-LG) in bovine milk [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes were subject to quality control, including (1) minimum call rates of 90% for individuals and 95% for loci and (2) exclusion of SNP with a minor allele frequency lower than 5% before imputation to Illumina BovineHD markers using IMPUTE2, v. 2.3.1 (Howie et al, 2011). Imputation was based on a reference population of 3,383 animals, including sires and siblings of some of the sampled cows, as described in detail by Gebreyesus et al (2016). Imputation accuracies were assessed based on the built-in cross-validation system implemented in IMPUTE2, which showed that imputation error was, on average, less than 1%.…”
Section: Genotypingmentioning
confidence: 99%
“…In the Danish data set, 278 cows were genotyped using the BovineSNP50 BeadChip. The remaining Danish Holstein cows were genotyped using the BovineHD BeadChip and used as reference to impute the 50K genotypes of the first part of the Danish cows to HD, as described by Gebreyesus et al (2016).…”
Section: Genotypes and Imputationmentioning
confidence: 99%